PERBANDINGAN KPS DAN HASIL BELAJAR MENGGUNAKAN METODE EKSPERIMEN LABORATORIUM NYATA DAN MAYA - Dita F. Karlinda; Agus Suyatna; Abdurrahman - (Jurnal Pembelajaran Fisika, 2013)
Experiments need to be conducted in order to develop scientific thinking in a systematic, objective, critical and rational and training Science Process Skills (SPS) students but the experimental method is rarely done in schools due to lack of lab equipment in the lab. The purpose of this research was to determine differences in SPS and student learning achievement caused by the use of experimental methods and to investigate the interaction between the use of experimental methods and the prior knowledge when viewed from the acquisition of SPS score and the learning achievement of student. The research design was factorial design and hypothesis testing using univariate tests. Mean of student SPS scores who experiment in virtual laboratory was 18.6 and 71.4 for their learning achievement. KPS score who experiment in real laboratory was 17.7 and 60.2 for their learning achievement. Univariate test results showed no effect of the experimental method to the SPS and t learning achievement of students. Obtained a significant interaction between the experimental method and prior knowledge when viewed from KPS score and learning achievement.Keywords: prior knowledge, SPS, learning achievement, real labs and virtual labs.